2020
DOI: 10.1016/j.msea.2019.138844
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal softening of Ti-metallic glasses during nanosecond laser shock peening

Abstract: Nanosecond laser shock peening (NLSP) has been proved to be an effective way to enhance the mechanical properties of metallic components through modifying the surface microstructures. However, the micromechanism of structure and property fluctuations induced by shock wave propagation is still limited due to the intrinsic defects in crystalline materials. Here, NLSP treatment has been performed into the Ti-metallic glasses. Owing to the absence of dislocations, grain boundary and phase segregation, the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 40 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…4e) might be due to dislocation burst or initiation of cracking. The pop-in events imply a change to plastic deformation and also indicates formation of localised inhomogeneous plastic flow under loading [29]. However, no crystalline defects have been observed from the load-depth graph.…”
Section: Microhardnessmentioning
confidence: 92%
See 1 more Smart Citation
“…4e) might be due to dislocation burst or initiation of cracking. The pop-in events imply a change to plastic deformation and also indicates formation of localised inhomogeneous plastic flow under loading [29]. However, no crystalline defects have been observed from the load-depth graph.…”
Section: Microhardnessmentioning
confidence: 92%
“…In the LE/HF-LSPwC, it was observed that above a specific fluence range (19.98 J/cm 2 ) direct ablation occur, which explain a transition As-received LE/HF-LSP (without coating) @19.98 J/cm 2 LE/HF-LSP (without coating) @21.21 J/cm 2 LE/HF-LSP (without coating) @24.14 J/cm 2 LE/HF-LSP (Vinyl + Quartz) @9.025 J/cm 2 LE/HF-LSP (Vinyl + Quartz) @42.12 J/cm 2 LE/HF-LSP (Vinyl + Soda lime glass) @96.27 J/cm 2 LE/HF-LSP (Vinyl + Soda lime glass) @102. 29 from compressive to tensile stresses in the material. Furthermore, this also adds up the reason i.e., the existence of a selective range of energy irradiation with a minimal ablation of matrix which has clearly attributed to the surface topography change and direct ablation where no coatings were used [34].…”
Section: Residual Stressmentioning
confidence: 99%